Management of Diverticular Disease in the Setting of Other Colorectal Pathology: Data on Simultaneous Issues in Segmental Colitis, Inflammatory Bowel Disease, Cancer, and Complications - Ghalyaie, Nasrin (Clinics in Colon and Rectal Surgery, 2018)
Diverticulosis of the colon is a very common anatomical condition. In the Western world, it affects more than 70% of over 65 years old population and represents the fifth most important gastrointestinal disease in terms of health care costs in Western countries. The diagnosis of diverticular disease and diverticulitis can be challenging. Often, there is overlap with other colonic pathologies, such as segmental colitis, ischemia, inflammatory bowel disease, cancer, or infectious colitis. Management of diverticular disease in these settings might be different.
Keywords: acute diverticulitis; segmental colitis associated with diverticulosis; inflammatory bowel disease